2001
DOI: 10.1287/orsc.12.6.683.10086
|View full text |Cite
|
Sign up to set email alerts
|

Keiretsu, Governance, and Learning: Case Studies in Change from the Japanese Automotive Industry

Abstract: The "keiretsu" structuring of assembler-supplier relations historically enabled Japanese auto assemblers to remain lean and flexible while enjoying a level of control over supply akin to that of vertical integration. Yet there is much talk currently of breakdown in keiretsu networks. This paper examines some recent developments in Japanese parts supply keiretsu.We argue that keiretsu relationships are drifting from "hybrid" or "network" (i.e., keiretsu) governance modes toward the extremes of arms-length contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(128 citation statements)
references
References 37 publications
2
118
1
4
Order By: Relevance
“…They found that many firms develop competencies in a given technological field (as measured by patents) even through they do not actively participate in the relevant product market. Similar findings have been reported in the aerospace and the automotive industries i.e., firms invest in knowledge of components even if the components are fully sourced through the market (Fine, 1998;Brusoni et al, 2001;Takeishi, 2002;Ahmadjian and Lincoln, 2001 Innovation within a product architecture requires not only the integration of individual components but also the coordination of interactions between different components. While technological progress in components along pre-existing trajectories allow for new innovations, these innovations may vary in their extent of "changes" in interactions between components (e.g., Henderson and Clark, 1990;Christensen, 1992;Henderson, 1995).…”
Section: Firm's Vertical Scope and Management Of Non-radical Technolosupporting
confidence: 66%
“…They found that many firms develop competencies in a given technological field (as measured by patents) even through they do not actively participate in the relevant product market. Similar findings have been reported in the aerospace and the automotive industries i.e., firms invest in knowledge of components even if the components are fully sourced through the market (Fine, 1998;Brusoni et al, 2001;Takeishi, 2002;Ahmadjian and Lincoln, 2001 Innovation within a product architecture requires not only the integration of individual components but also the coordination of interactions between different components. While technological progress in components along pre-existing trajectories allow for new innovations, these innovations may vary in their extent of "changes" in interactions between components (e.g., Henderson and Clark, 1990;Christensen, 1992;Henderson, 1995).…”
Section: Firm's Vertical Scope and Management Of Non-radical Technolosupporting
confidence: 66%
“…The description of intermediate facilities appears to have similarities with typical materials handling facilities at supplier parks (Mathisson-Ölmertz & Johansson, 2000, Howard et al, 2006, which appear to be increasingly common in automotive and other industries (Howard et al, 2006). Supplier parks are usually in close proximity to the OEM (in a Japanese context supplier parks may be linked to Keiretsu relationships, Ahmadjian and Lincoln, 2001). The reasons for locating facilities at a supplier park are: to enable sequential just-in-time deliveries (Larsson, 2002); to increase delivery reliability due to shorter transport distances (Reichhart & Holweg, 2008); to decrease transport cost (Millington et al, 1998); to increase face-to-face contact and to enable quicker problem resolution and better mutual understanding (Frigant & Lung, 2002).…”
Section: Insert Figure 2 Herementioning
confidence: 97%
“…Thus, the expected number of special …rms is H . 2 1 Note that we do not consider any marginal cost of production. This allows us to neglect any vertical foreclosure motive linked to the vertical integration decisions.…”
Section: The Modelmentioning
confidence: 99%
“…On March 4, 2013 the University of Bologna jointly with Unindustria Bologna created AlmaCube Limited Company. 2 This is an innovative way to prompt the creation of start-up. Indeed, for the …rst time in Italy, institutional sponsors not only give …nancial, administrative and …scal facilities to new start-up but become partners by taking a relevant part of the entrepreneurial risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation